PENGARUH MODEL ACTIVE LEARNING TERHADAP PENINGKATAN MOTIVASI SISWA DALAM PEMBELAJARAN RENANG TANPA KOLAM - Cheryl Athya, Mahardini (Jurnal Pedagogik Olahraga, 2026)
This study aims to examine the effect of implementing the Active Learning model on student learning motivation in swimming lessons without a pool. This study used a quantitative approach with a one-group pretest-posttest design involving 32 students as research subjects. Learning motivation was measured using a questionnaire that had undergone content validity and reliability testing. Then, it was analyzed using paired sample t-tests and effect sizes to assess the statistical and practical significance of the treatment. The results showed a trend toward an increase in student learning motivation scores after implementing Active Learning, but this increase was not statistically significant. This finding indicates that Active Learning in swimming lessons without a pool has not been able to provide a meaningful impact on student learning motivation in the short term. The study's conclusion confirms that the effectiveness of active learning is greatly influenced by the match between the pedagogical approach and the characteristics of skills that require sensory and kinesthetic experiences. Therefore, more adaptive and contextual learning strategies are needed in situations with limited facilities. Keywords: Active Learning, learning motivation, swimming lessons, swimming without a pool, physical education